The Effect of Product Quality and Brand Image on Customer Loyalty With Customer Satisfaction As A Mediation Variable (Study On Customers Elita Veil in Yogyakarta) - Ningrum, Putri Nurkusuma; Harahap, Ridho Satrio; Wibisono, Dimas; Syah, Toufan Aldian (DAS Institute, 2022)
This study empirically examines the effect of product quality and brand image on customer loyalty, with customer satisfaction as a mediating variable on Elita's veil customers in Yogyakarta. This type of research is quantitative research with associative design. The population of this research is the Elita Veil customers in Yogyakarta. The sampling technique is a purposive sampling method and research data by 100 respondents—data collection through Google form by distributing questionnaires. The analytical method used is multiple linear regression. The data analysis technique used Smart Partial Least Square (PLS). The results showed: that product quality has a positive effect on customer satisfaction, brand image has a positive effect on customer satisfaction, product quality has an effect on customer satisfaction, brand image has no effect on customer satisfaction, product quality has an effect on customer loyalty, product quality has a positive effect on customer loyalty, brand image has no positive effect on customer loyalty, customer satisfaction has a positive effect on customer loyalty, customer satisfaction mediates product quality on customer loyalty, customer satisfaction does not mediate brand image on customer loyalty.